2016
DOI: 10.1021/acs.jced.5b00892
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization Enthalpies and Vapor Pressures of Some Insect Pheromones by Correlation Gas Chromatography

Abstract: The vaporization enthalpies and vapor pressures of the following insect pheromones at T/K = 298.15 have been evaluated by correlation gas chromatography: Z-8-dodecenyl acetate, Z-4-tridecenyl acetate, E-11-tetradecenyl acetate, E,E-9,11-tetradecadienyl acetate, Sethyl (2E,4E)-3,7,11-trimethyl-2,4-dodecadienoate, R,S-2-propynyl (2E,4E)-3,7,11-trimethyl-2,4-dodecadienoate, and Z-13-octadecenyl acetate. Also evaluated are vapor pressures as a function of temperature from T/K = 298.15 to 500 which have been fit to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Experimental data of vaporization enthalpies have essentially been extracted for this work from the large collection of Acree, Jr. and Chickos [ 8 ] and Chickos et al [ 10 , 11 , 12 , 13 , 14 ], supplemented by recent data from a number of further authors publishing experimental vaporization values of several acetophenones [ 23 ], aliphatic tertiary amines [ 24 ], azidomethyl- N -nitrooxazolidines [ 25 ], benzamides [ 26 ], benzocaine [ 27 ], bisabolol and menthol [ 28 ], crown ethers [ 29 ], N , N -dialkyl monoamides [ 30 ], fenpropidin and phencyclidine [ 31 ], flavors [ 32 ], long-chain fluorinated alcohols [ 33 ], whiskey- and metha-lactone [ 34 ], halogenated fluorenes [ 35 ], ibuprofen and naproxen [ 36 ], imidazo[1,2- a ]pyrazine and phthalazine [ 37 ], insect pheromones [ 38 ], morpholines [ 39 ], organo(thio)phosphates [ 40 ], dialkyl phthalates [ 41 ], nitrogen heteroaromatics [ 42 ], phenylimidazoles [ 43 ], 2-acetylthiophene [ 44 ], dicarboxylic n -pentyl esters [ 45 ], and cyclic amines, ethers and alcohols [ 46 ]. The result of the atom-group parameters, based on 3581 compounds, is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data of vaporization enthalpies have essentially been extracted for this work from the large collection of Acree, Jr. and Chickos [ 8 ] and Chickos et al [ 10 , 11 , 12 , 13 , 14 ], supplemented by recent data from a number of further authors publishing experimental vaporization values of several acetophenones [ 23 ], aliphatic tertiary amines [ 24 ], azidomethyl- N -nitrooxazolidines [ 25 ], benzamides [ 26 ], benzocaine [ 27 ], bisabolol and menthol [ 28 ], crown ethers [ 29 ], N , N -dialkyl monoamides [ 30 ], fenpropidin and phencyclidine [ 31 ], flavors [ 32 ], long-chain fluorinated alcohols [ 33 ], whiskey- and metha-lactone [ 34 ], halogenated fluorenes [ 35 ], ibuprofen and naproxen [ 36 ], imidazo[1,2- a ]pyrazine and phthalazine [ 37 ], insect pheromones [ 38 ], morpholines [ 39 ], organo(thio)phosphates [ 40 ], dialkyl phthalates [ 41 ], nitrogen heteroaromatics [ 42 ], phenylimidazoles [ 43 ], 2-acetylthiophene [ 44 ], dicarboxylic n -pentyl esters [ 45 ], and cyclic amines, ethers and alcohols [ 46 ]. The result of the atom-group parameters, based on 3581 compounds, is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data of vaporization enthalpies have essentially been extracted for this work from the large collection of W. E. Acree Jr. and J. S. Chickos [8] and J. S. Chickos et al [10][11][12][13][14], supplemented by recent data from a number of further authors publishing experimental vaporization values of several acetophenones [23], aliphatic tertiary amines [24], azidomethyl-N-nitro-oxazolidines [25], benzamides [26], benzocaine [27], bisabolol and menthol [28], crown ethers [29], N,N-dialkyl monoamides [30], fenpropidin and phencyclidine [31], flavors [32], long-chain fluorinated alcohols [33], whiskey-and methalactone [34], halogenated fluorenes [35], ibuprofen and naproxen [36], imidazo[1,2-a]pyrazine and phthalazine [37], insect pheromones [38], morpholines [39], organo(thio)phosphates [40], dialkyl phthalates [41], nitrogen heteroaromatics [42], phenylimidazoles [43], 2-acetylthiophene [44], dicarboxylic n-pentyl esters [45], and cyclic amines, ethers and alcohols [46]. The result of the atom-group parameters, resting on 3581 compounds, is summarized in Table 1.…”
Section: Enthalpy Of Vaporizationmentioning
confidence: 99%
“…78 Vapor pressures p GLC for unsaturated FAME subsequently published by Lipkind et al 70 (based on p GLC for FAME 78 ) were found to differ by (27 to 87) percent from Model for the Thermodynamic Properties of a Biodiesel Fuel developed in 2009 in NIST, Boulder, 101 and in case of methyl oleate to differ by 67% from those directly measured in 2017 by another scientific group in NIST, Boulder. 102 There are also other papers reporting p GLC obtained with CGC methodology 27,92,103 based on either vapor pressures for FAME recommended by van Genderen et al 99 or p GLC based on them. 78 Moreover, biased FAME p GLC 78 values were used by other researchers, for example, for parametrization of PC-SAFT EOS, 104 CPA EOS, 105−107 validation of a newly developed force field, 108 development of a group contribution method for estimation of PC-SAFT EOS parameters, 109 and development of a group contribution method for estimation of vapor pressures at 298.15 K. 96 5.1.3.…”
Section: N-alkanesmentioning
confidence: 99%